Multiplicity results for the Neumann boundary value problem - Atslega, Svetlana (Mathematical Modelling and Analysis, 2007)
We provide multiplicity results for the Neumann boundary value problem, when the second order differential equation is of the form x” = f(x). First Published Online: 14 Oct 2010